Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acsfoodscitech.2c00212
|View full text |Cite
|
Sign up to set email alerts
|

Spray Drying Conditions of Antioxidant and Anti-inflammatory Polyphenols in Microcapsules of Ultrasound Assisted Extract of Salvilla (Buddleja scordioides Kunth)

Abstract: The consumption of natural products against gastrointestinal disorders has been increasing. Although there are pharmaceutical treatments, they present side effects, so new alternatives like nutraceuticals are investigated. Salvilla is used as a traditional treatment due to its bioactive phenolic content. Such extracts may be obtained by ultrasound assisted extraction (UAE) and microencapsulated to preserve them and develop a nutraceutical product. Therefore, salvilla extract was obtained by UAE and microencaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The methods for extracting and stabilizing bioactive compounds from plant materials and evaluating their biological activity were major topics covered in oral and poster presentations. For instance, Maci ́as-Corteś et al 1 evaluated spray drying conditions to microencapsulate extracts obtained by ultrasound-assisted extraction of salvilla (an aromatic plant distributed in Mexico). The authors reported a high antioxidant activity of the extract, which was preserved by microencapsulation.…”
mentioning
confidence: 99%
“…The methods for extracting and stabilizing bioactive compounds from plant materials and evaluating their biological activity were major topics covered in oral and poster presentations. For instance, Maci ́as-Corteś et al 1 evaluated spray drying conditions to microencapsulate extracts obtained by ultrasound-assisted extraction of salvilla (an aromatic plant distributed in Mexico). The authors reported a high antioxidant activity of the extract, which was preserved by microencapsulation.…”
mentioning
confidence: 99%